Formation of Gold Microstructures By Galvanic Reduction on Carbon Surfaces. - Mohamed, Norita; Yap, Chin Yean; Aminuddin, Norazlina; Darus, Hamzah (2005)

(untitled)
Electrodeposition of metal nanocrystals onto carbon surfaces widely investigated.